A multi‐methods yarn about SMART Recovery: First insights from Australian Aboriginal facilitators and group members. (8th March 2021) - Dale, Elizabeth; Lee, K. S. Kylie; Conigrave, Katherine M.; Conigrave, James H.; Ivers, Rowena; Clapham, Kathleen; Kelly, Peter J.
Abstract: Introduction: SMART Recovery is a popular mutual support group program. Little is known about its suitability or perceived helpfulness for Indigenous peoples. This study explored the cultural utility of SMART Recovery in an Australian Aboriginal context. Methods: An Indigenous‐lensed, multi‐methods, exploratory study design was used to develop initial evidence of: (i) attributes of Aboriginal SMART Recovery facilitators and group members; (ii) characteristics of Aboriginal‐led SMART Recovery groups; (iii) perceived acceptability and helpfulness of SMART Recovery; and (iv) areas for potential improvement. Data were collected by synthesising Indigenous qualitative methods (research topic and social yarning) with western qualitative and quantitative methods (participant surveys, program adherence rating scale, group observations and field notes). Data were analysed using thematic analysis. Results: Participants were a culturally diverse sample of male and female Aboriginal facilitators ( n  = 10) and group members ( n  = 11), aged 22–65 years. Aboriginal‐led SMART Recovery groups were culturally customised to suit local contexts. Program tools 'goal setting' and 'problem solving' were viewed as the most helpful. Suggested ways SMART Recovery could enhance its cultural utility included: integration of Aboriginal perspectives into facilitator training; creation of Aboriginal‐specific program and marketing materials; and greater community engagement and networking. Participants proposed an Aboriginal‐specific SMART Recovery program. Discussion and Conclusions: This study offers insights into Aboriginal peoples' experiences of SMART Recovery. Culturally‐informed modifications to the program were identified that could enhance cultural utility. Future research is needed to obtain diverse community perspectives and measure health outcomes associated with group attendance.